A simple new non‐invasive sweat indicator test for the diagnosis of diabetic neuropathy. Issue 5 (15th April 2013) - Papanas, N.; Boulton, A. J. M.; Malik, R. A.; Manes, C.; Schnell, O.; Spallone, V.; Tentolouris, N.; Tesfaye, S.; Valensi, P.; Ziegler, D.; Kempler, P.
Abstract A simple non‐invasive indicator test (Neuropad®) has been developed for the assessment of sweating and, hence, cholinergic innervation in the diabetic foot. The present review summarizes current knowledge on this diagnostic test. The diagnostic ability of this test is based on a colour change from blue to pink at 10 min, with excellent reproducibility, which lends itself to patient self‐examination. It has a high sensitivity (65.1–100%) and negative predictive value (63–100%), with moderate specificity (32–78.5%) and positive predictive value (23.3–93.2%) for the diagnosis of diabetic peripheral neuropathy. It also has moderate to high sensitivity (59.1–89%) and negative predictive value (64.7–91%), but low to moderate specificity (27–78%) and positive predictive value (24–48.6%) for the diagnosis of diabetic cardiac autonomic neuropathy. There are some data to suggest that Neuropad can detect early diabetic neuropathy, but this needs further evaluation. It remains to be established whether this test can predict foot ulceration and amputation, thereby contributing to the identification of high‐risk patients. Diabet. Med. 30, 525–534 (2013)